The 4-girth-thickness of the complete multipartite graph - Christian Rubio-Montiel (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2019)
The g-girth-thickness θ(g, G) of a graph G is the smallest number of planar subgraphs of girth at least g whose union is G. In this paper, we calculate the 4-girth-thickness θ(4, G) of the complete m-partite graph G when each part has an even number of vertices.